Mechanisms underlying the development of weakness in idiopathic inflammatory myopathies: an in vitro single muscle fibre contractility study - Henning, Franclo (Division of Exercise Science and Sports Medicine, 2019)
Introduction: Polymyositis (PM), dermatomyositis (DM) and necrotising autoimmune myopathy (NAM) form part of the spectrum of idiopathic inflammatory myopathies (IIMs). Although the pathogenic mechanisms are different, the unifying feature is that of weakness caused, in some way or another, by an inflammatory attack on muscle. The mechanism by which weakness develops is still unclear, but experimental animal data suggest that dysfunction of the contractile apparatus might contribute to muscle weakness in these conditions. This study investigated the contractile function of single muscle fibres from patients with IIMs in vitro. Methods: Muscle biopsies obtained from patients with IIMs and healthy controls were dissected and chemically permeabilised. Single muscle fibres were dissected out and subjected to contractility measurement based on standard protocols utilising a permeabilised single fibre system. Specific force (SF; maximum force normalised to cross-sectional area), was calculated for each fibre and compared between the two groups. In addition, maximum shortening velocity and power output were assessed in some of the fibres, and calcium sensitivity in the rest. The myosin heavy chain composition of each fibre was determined by means of gel electrophoresis. Results: A total of 178 fibres from IIM cases and 174 fibres from controls were studied. Specific (normalised) force was 23%, 24% and 29% lower in the IIM group for all fibre types combined, type I fibres, and type IIa fibres, respectively. Shortening velocity and maximum power output were significantly higher in the IIM group for both type I and IIa fibres, compared to controls, while calcium sensitivity was higher in type IIa fibres from IIM cases than controls. Discussion: The findings from this study suggest that weakness in IIMs may, at least in part, be caused by dysfunction of the contractile apparatus leading to impaired contractile force. The higher shortening velocity, power output and calcium sensitivity in fibres from IIM cases probably represents compensatory mechanisms. Although the mechanism by which contractile function is affected has not been investigated, animal studies suggest a role for TNF-α. The findings of this study provide a basis for further investigation into the mechanisms underlying weakness in IIMs.